PEMETAAN INOVASI BANDARA INTERNASIONAL JAWA BARAT DENGAN BISNIS MODEL CANVAS - Robi Awaluddin (Jurnal Mantik Penusa)
PT Bandar udara Internasional Jawa Barat (PT BIJB) is a Regional Owned Enterprise (BUMD) formed by the West Java Provincial Government through regional law No. 222013 was established on November 24, 2014. PT BIJB is responsible for the construction of the land side and the development and operation of West Java International Airport, also developing Kawasan Aerocity which is integrated with the Airport to develop the surrounding economy.BIJB is located inMajalengka, West Java. This study used to identify the vision and mission also social impact of this airport, use a qualitative descriptive approach with interviews, observation, surveys and literature studies. sample selection is purposive with company internal resource persons. from this research it is known that currently the PT BIJB has a vision, mission and core value of the company, also has a strategy of segmentation, target and positioning and corporate value. from mapping the 9 elements of the business model canvas, it is known that the most important thing is that there is a futuristic airport concept innovation by creating an airport concept that has natural nuances, an open airport and integrated with aerocity on its value preposition, on customer segments PT BIJB recruits local workers to become technical workers in airport